Older Men as Learners: Irish Men's Sheds as an Intervention. (May 2015) - Carragher, Lucia; Golding, Barry
To date, little attention has been placed on older men (aged 50+ years) as learners, with much of the literature on adult learning concerned with younger age-groups and issues around gender equity directed mainly at women. This article examines the impact of community-based men's sheds on informal and nonformal learning by older men in Ireland. It considers older men's attitudes to learning, learning behavior, and the noncognitive attributes—motivation, perseverance, and beliefs about capabilities—that underpin learning behavior. This descriptive study used a mixed-methods approach, involving questionnaires and focus groups, with all sheds registered with the Irish Men's Sheds Association invited to participate. It is concluded that men's sheds provide space for hands-on learning activities that add value to the lives and experiences of men beyond work, fostering a yearning to carry on learning. Crucially, shed-based conversations have an important role in helping older men with difficult life transitions and are an important site for future studies of masculinity in later life.